Predictors of short-term repetition of self-harm among patients admitted to an emergency room following self-harm: A retrospective one-year cohort study. (December 2017) - Kawahara, Yoko Yoshida; Hashimoto, Satoshi; Harada, Masahiro; Sugiyama, Daisuke; Yamada, Shu; Kitada, Maki; Sakurai, Toshihiro; Takahashi, Takeshi; Yamashita, Kensho; Watanabe, Kenjiro; Mimura, Masaru; Fujisawa, Daisuke
Abstract: We conducted a retrospective chart-review study, examining predictors of the repetition of short-term self-harm (<1 month and <6 months) among the patients who were admitted to an emergency department in Japan following self-harm. A total of 405 patients were enrolled and were followed-up for a subsequent one year. The incidence of repeated self-harm within one- and six- months were 6.4% and 13.1%, respectively. Cox's proportional hazards model analyses demonstrated that history of self-harm and comorbid physical illness were associated with repeated self-harm within one month. The patients who lived alone and who were directly discharged from the emergency room after referral to a psychiatrist were at higher risk for repeated self-harm within both one and six months. Living on public assistance and having been discharged from psychiatric wards within the past 12 months were associated with repetition within six months. These risk factors should be incorporated into routine assessment at an emergency room, and elaborate follow-up plan should be provided to the patients with these risk factors upon discharge from the emergency room. Further prospective studies are warranted, addressing more comprehensive factors that are associated with short-term risk for self-harm and suicide. Highlights: A high rate of repeated self-harm within short term are found. Repetition rate of SB after discharge from an emergency room is high. Previous self-herm and physical problems are immediate risks for repetition. Patients who live alone are at risk for repetition within one and six months. Poorer socioeconomic status are at risk for repetition within six months.